Napływ bezpośrednich inwestycji zagranicznych do krajów Azji Wschodniej, Południowej oraz Południowo-Wschodniej w latach 2000-2007 - Adamczyk, Marzena; Piasecka-Głuszak, Agnieszka (The Foreign Direct investments inflows into South, East, and South-East Asia between 2000 and 2007, 2009)
Processes taking place in the world economy, competition in international markets, countries changing their economic policy, liberalization of economies make flows of capital easier, first of all foreign direct investments. This article’s objective is to present the volume of foreign direct investments inflows into South, East, and South-East Asia between 2000 and 2007. The analysis is based on the World Investment Report 2008 of the United Nations Conference on Trade and Development (UNCTAD) for subject Transnational Corporations and the Infrastructure Challenge
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2009; Nr 67, s. 284-294